Modernity at gunpoint : firearms, politics, and culture in Mexico and Central America - Esch, Sophie (Illuminations (Pittsburgh, Pa.), 2018)
"Modernity at Gunpoint provides the first study of the political and cultural significance of weaponry in the context of major armed conflicts in Mexico and Central America. In this highly original study, Sophie Esch approaches political violence through its most direct but also most symbolic tool: the firearm. In novels, songs, and photos of insurgency, firearms appear as artifacts, tropes, and props, through which artists negotiate conceptions of modernity, citizenship, and militancy. Esch grounds her analysis in important rereadings of canonical texts by Martín Luis Guzman, Nellie Campobello, Omar Cabezas, Gioconda Belli, Sergio Ramirez, Horacio Castellanos Moya, and others. Through the lens of the iconic firearm, Esch relates the story of the peasant insurgencies of the Mexican Revolution, the guerrilla warfare of the Sandinista Revolution, and the ongoing drug-related wars in Mexico and Central America, to highlight the historical, cultural, gendered, and political significance of weapons in this volatile region"--